2020
DOI: 10.1111/eci.13205
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent incidence and risk for myocardial infarction in patients with alcoholic cirrhosis

Abstract: Background It remains unsettled whether alcoholic cirrhosis is a risk factor for myocardial infarction (MI). Methods We used data from nationwide healthcare registries to study all Danes diagnosed with alcoholic cirrhosis in 1996‐2014, and five controls were matched to each of them on gender and age. We excluded everyone with ischaemic heart disease and used Cox regression to estimate the incidence rate ratio of MI adjusted for potential cardiovascular confounders. Further, we described the MI‐risk with non‐MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
3
2
0
Order By: Relevance
“…We found that cirrhosis was not a risk factor for AMI. This finding is consistent with our previous study, ( 9 ) and here we show that—among patients with cirrhosis—decompensation was a strong risk factor for AMI. We also extend our previous study by highlighting that AMI is highly fatal in patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found that cirrhosis was not a risk factor for AMI. This finding is consistent with our previous study, ( 9 ) and here we show that—among patients with cirrhosis—decompensation was a strong risk factor for AMI. We also extend our previous study by highlighting that AMI is highly fatal in patients with cirrhosis.…”
Section: Discussionsupporting
confidence: 94%
“…We have found that patients with cirrhosis have more severe and extensive coronary artery disease than controls, ( 8 ) yet they do not have an increased risk of acute myocardial infarction (AMI). ( 9 ) In addition, a recent meta‐analysis found no apparent association between cirrhosis and risk of ischemic stroke (IS), but all five meta‐analyzed studies were from Asia, and relative risks ranged from 0.32 to 1.22. ( 10 ) Thus, risks of AMI and IS in patients with cirrhosis remain poorly defined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that patients with liver cirrhosis had an increased risk of ischemic stroke (aHR, 1.7; 95% CI, 1.3‐2.3) and venous thromboembolism (aHR, 2.0; 95% CI, 1.5‐2.6), but not myocardial infarction (aHR, 0.7; 95% CI, 0.5‐0.9). Similar findings on the lack of association between liver cirrhosis and myocardial infarction are described by Deleuran et al 37 …”
Section: Discussionsupporting
confidence: 89%
“…CI, confidence interval; HR, hazard ratio TA B L E 3 Incidence rates, number of events, and adjusted hazard ratios of thromboembolic and bleeding complications, during 0-1 year of follow-up, stratified by baseline values, in patients with atrial fibrillation or flutter ), but not myocardial infarction (aHR, 0.7; 95% CI, 0.5-0.9). Similar findings on the lack of association between liver cirrhosis and myocardial infarction are described by Deleuran et al 37 Søgaard et al 13 investigated the risk of venous thromboembolism in patients with liver cirrhosis, compared to the general population.…”
Section: Contribution To the Literaturesupporting
confidence: 62%